Analysis of Factors Affecting Poverty in Eastern Indonesia - Quriah Silvia Ningsih; Novi Tri Putri (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to analyze the effect of per capita income, length of schooling, and unemployment to on poverty in Eastern Indonesia. A panel regression model was used. The data used consisted of 11 provinces from 2016 to 2022. The research results show per capita income has a significant negative effect on poverty. Years of schooling and the unemployment rate have a significant positive effect on poverty. Years of schooling and unemployment rates are the main factors influencing poverty in Eastern Indonesia. Meanwhile, per capita income and years of schooling can help reduce poverty in Eastern Indonesia. Thus, both central and regional governments should reduce the unemployment rate. They also should create the programs in order to increase the people’s income in Eastern Indonesia.